Evaluating Namibian macrophytic algae as dietary source for South African abalone (Haliotis midae) - Tsanigab, Salomon M. (Stellenbosch : University of Stellenbosch, 2009)
Thesis (Msc Food Sc (Food Science))--University of Stellenbosch, 2009.